The Indonesian Satpol-PP Model: Lessons for Local Governance and Public Order Enforcement in Decentralized States - Pelengkahu, Muhamad; Palengkahu, Rizjal; Kasim, Fajri M (Penerbit Mandalika Indonesia, 2026)
Decentralized governance often creates a gap between regulatory authority and enforcement capacity at the local level. This study examines the Indonesian Satuan Polisi Pamong Praja (Satpol-PP) as a model of subnational enforcement designed to address this challenge. This research employs a qualitative and comparative approach based on document analysis of legal frameworks, policy reports, and academic literature. It compares Satpol-PP with similar institutions in France, Germany, Canada, and the United States across key institutional dimensions. The findings show that Satpol-PP represents a hybrid civilian enforcement body operating under local government authority with administrative powers to enforce regional regulations and maintain public order. Compared to its international counterparts, Satpol-PP has a broader functional scope, strong political embeddedness, and a non-militarized character, though it faces challenges related to professionalism, legal clarity, and public legitimacy. Satpol-PP demonstrates that decentralized states can develop locally anchored, non-police enforcement mechanisms. While not universally replicable, its model offers valuable insights into institutional adaptability, civilian-based enforcement, and the importance of balancing local responsiveness with accountability and legal safeguards.